Prevalence of depression and health related quality of life among patients with diabetes mellitus and hypertension attending a secondary care hospital in district Faridabad, Haryana - Kamble, Bhushan; Rath, Rama Shankar; Misra, Puneet; Rai, Sanjay Kumar; Kant, Shashi (Indian Journal of Community Health, 2022)
Background: Diabetes mellitus (DM) and hypertension (HT) have significant effect on the mental health of the patient. and. We aimed to estimate the prevalence of depression, and the quality of life among patients with diabetes mellitus and hypertension who attended a secondary care hospital. Methods: A cross-sectional study was carried out among 618 patients who had DM and/or HT. PHQ-9 and WHO-BREF QOL questionnaire were administered to assess depression and health related quality of life respectively. Results: More than 2/3rd of patients had depression. Among those who had depression, nearly half (46%) had moderate depression and 2.1% had severe depression. The proportion of severely depressed patients was higher in diabetes mellitus group compared to the hypertension group. Patients that were depressed had poorer quality of life compared to non-depressed, and the difference was statistically significant. Conclusion: Patients with diabetes mellitus and hypertension may be screened for depression and managed accordingly.